Layered metal vanadates with different interlayer cations for high-rate Na-ion storage. Issue 27 (28th June 2019) - Huang, Haijian; Tian, Tian; Pan, Long; Chen, Xi; Tervoort, Elena; Shih, Chih-Jen; Niederberger, Markus
Abstract : The relationship between the interlayer metal ions and the Na-ion storage performance of layered metal vanadates is systematically explored. Abstract : Layer-structured metal vanadates have been regarded as promising candidates for high-rate Na-ion storage. However, without a detailed understanding of the relationship between the interlayer metal ions and the cycling performance, it remains a difficult task to systematically explore layered metal vanadates as high performance electrode materials. Herein, a series of metal vanadates with different interlayer cations such as Co 2+ and Zn 2+ are prepared and applied as Na-ion battery anodes. First principles simulations and ex situ X-ray diffraction measurements demonstrate that the Na-ion storage performance of the layered metal vanadates is closely related to the structural stress induced by Na + insertion, and the ion diffusion barrier, as well as the structural reversibility. In addition, a double-interlayer-cation metal vanadate, i.e., Co0.16 Zn0.09 V2 O5 · n H2 O, is reported for the first time as a high-rate Na-ion battery anode. This compound successfully combines the favorable features of Co0.25 V2 O5 · n H2 O and Zn0.25 V2 O5 · n H2 O, resulting in the best cycling performance. CV analysis and operando X-ray diffraction measurements reveal a large pseudocapacitive contribution and small volume change of Co0.16 Zn0.09 V2 O5 · n H2 O during cycling. Our study presents a versatile concept for the optimization of metal vanadates for Na-ion storage, which may open a promising direction for developing high-rate energy storage materials.